Analysis on the ecological impact of the Xiaolangdi Reservoir on the Yellow River Delta wetland and coastal areas - Shang, Wenxiu; Yan, Dengming; Peng, Shaoming; Wang, Yu; Ge, Lei; Shang, Yi (Frontiers in Earth Science, 2022)
Environmental water supplement through reservoir regulation is an important way to restore the deltaic coastal wetland. In order to quantify the impact of the reservoir on the deltaic coastal wetland ecosystem, this paper proposes a quantitative analysis method for the ecological impact and contribution rate of the reservoir, which compares the runoff status under the two scenarios of the presence or absence of the reservoir during the assessment period, and reveals the reservoir’s impact on and contribution rate to the runoff status and environmental water supplement conditions. The results show that from 2000 to 2019, through the regulation of the Xiaolangdi Reservoir, the drying up days at Lijin Section in the lower reaches reduced by 81.15d annually, the volume of water into the sea from April to June increased by 2.37 billion m³ and the environmental water supplement of the Yellow River Delta increased by 19.95 million m³. Com-pared with the period from 1980 to 1999, the natural runoff of the Yellow River decreased by 10.59% from 2000 to 2019, the measured runoff in the lower reaches decreased by 22.15%, and the water withdrawal in the lower reaches increased by 0.32 billion m³, which is not conducive to guarantee the environmental water volume in the Yellow River Delta wetland and coastal areas. The Xiaolangdi Reservoir reversed the adverse effects of runoff and water withdrawal, and ensured the continuous ecological improvement in the Yellow River Delta and coastal areas, providing the respective contribution rate of 187.85% and 125.83% to the prevention of drying up at Lijin Section and the increase in the volume of water into the sea in the critical period.